Aristotle's consequentialism - Kary, Dan Austin, 1984- (2008)
Thesis (M.A.)--Memorial University of Newfoundland, 2008. Philosophy Includes bibliographical references (leaves 58-59) This thesis is an investigation into Aristotle's ethical thought with the goal of showing that he is both a virtue ethicist, and a consequentialist philosopher. It carefully examines what he says, and analyzes it with a consequentialist lens and compares Aristotle to various consequentialist schools of thought to show some similarity. It also attempts to reconcile both consequentialism and virtue ethics to show that the theories need not be in opposition and that Aristotle gives a theory where they co-exist by answering two distinct questions: What should I do? and What kind of Person should I be?